Industry Academia and Government Collaboration to Reduce Gaps in Software Engineering: Applications for Students and Professionals in Career Transition - Marques, Denis; Rocha, Richard; Santos, Bruna; Pacheco, Felipe; Rodrigues, Cleyton Mario de Oliveira; Santos, Wylliams Barbosa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
The development of skills in Software Engineering disciplines often faces challenges when applied to real projects in the software industry. An effective practice to overcome these difficulties is collaboration between industry and academia. This collaboration aims to strengthen the exchange of knowledge between the two contexts, promoting the advancement of industry through Research and Development (R&D), and in academia, applying knowledge in real contexts and even funding research. This study explores application development and the perceptions of undergraduate, master’s and doctoral students in Computer Engineering, as well as professionals in career transition (with Now and Low Code profiles), about projects with real clients and collaboration policies between industry and academia.